Correlation between Severity of Knee Osteoarthritis and Serum Levels of Cartilage Oligomeric Matrix Protein - Kambayana, Gede; Kurniari, Pande; Andriyasa, Andriyasa; Putra, T R (Indonesian Rheumatology Association, 2014)
Background: The sensitivity of radiographic examination in the diagnosis and severity assessment of knee osteoarthritis (OA) is still low. Various attempts have been made to find more reliable indicators of cartilage damage. One potential marker is cartilage oligomeric matrix protein (COMP), a substance that in previous animal studies had been shown to be released in proportion to the extent of joint cartilage damage.Objective: To evaluate the correlation between the severity of knee OA and serum level of COMP in human with normal renal function. Methods: This was a cross-sectional study performed at the outpatient clinic in Department of Internal Medicine, Sanglah Hospital, Denpasar. The diagnosis of knee OA was based on the American College of Rheumatology (ACR) criteria. The degreeof knee OA severity was determined by using the Kellgren-Lawrence criteria, while COMP values were checked by enzyme-linked immunosorbent assay (ELISA) method.Results: Forty five patients who were recruited were examined: 19 (42.2%) were female and 26 (57.8%) were male. The mean age of patients was 64.1Â±7.1 years. There were 4.4%, 26.7%, 46.7%, and 22.2% patients who had grade 1st, 2nd, 3rd, and 4th degree joint damage based on the Kellgren-Lawrence score, respectively. Mean serum level of COMP was 1081.4 ng/mL. We found a significant correlation ofthe severity of knee OA with serum level of COMP (r = 0.41, p = 0.005).Conclusion: Among the patients in this study, there was a significant correlation between the severity of joint damage in knee OA and serum level of COMP.